Study of metformin in diabetes mellitus with stage 3 and 4 chronic kidney disease - Peeyush, D.; Lamsal, M.; Maskey, R.; Sharma, S.K. (Journal of Diabetes and Endocrinology Association of Nepal, 2020)
Background: Chronic Kidney Disease is one of the major complications of Diabetic patients. Cardiovascular mortality increases in patient with diabetes and more so with diabetic CKD. Clinician treating diabetic CKD finds option limited as metformin is considered contraindicated when serum creatinine is greater than 1.5 mg/dl in males and greater than 1.4 mg/dl in females. The primary aim of the study is to evaluate the efficacy of metformin in terms of glycemic control in patient with diabetic stage 3 and 4 CKD. Methods: This is Randomised open labelled clinical trial done in the Department of Internal Medicine, B. P. Koirala Institute of Health Sciences, Dharan, Nepal. Primary end point were glycemic status at 6 months as defined by with fasting, post prandial blood sugar, glycosylated hemoglobin in comparison to baseline. Results: Altogether 73 diabetic patients with diabetic CKD stage 3 and 4 were included in the study. 41 patients were included in insulin group and 32 patients in metformin group. In metformin group, the fasting and past prandial blood sugar declined progressively compared to insulin group, where fasting and post prandial blood sugar declined more rapidly. Conclusions: Metformin is found to be efficacious in diabetic CKD as it had already proved to be effective in diabetes without CKD. In this study metformin was not associated with lactic acidosis and the level of lactate with metformin treatment was similar to that of treatment with insulin. The vast majority of case reports relating metformin to lactic acidosis report at least one other disease/illness that could result in lactic acidosis. Despite increasing disregard of contraindications to metformin by physicians, the incidence of lactic acidosis has not increased, as does the result of this study. So metformin may be safe even in patients with diabetic CKD stage 3 and 4.